Search for the standard model Higgs boson in the p(p)over-bar -> ZH -> v(v)over-barb(b)over-bar channel - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. -L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2006)
We report a search for the standard model (SM) Higgs boson based on data collected by the D0 experiment at the Fermilab Tevatron Collider, corresponding to an integrated luminosity of 260 pb(-1). We study events with missing transverse energy and two acoplanar b jets, which provide sensitivity to the ZH production cross section in the nu nu bb channel, and to WH production when the lepton from the W ->center dot nu decay is undetected. The data are consistent with the SM background expectation, and we set 95% C.L. upper limits on sigma(pp -> ZH/WH) x B(H -> bb) from 3.4/8.3 to 2.5/6.3 pb, for Higgs-boson masses between 105 and 135 GeV.